THE EDUCATIONAL PARADIGM AND THE NEW VISION OF THE MAN - Pizano Chávez, Guillermina (2014)
This article presents the significance that the educational models and paradigms have in our educational praxis. It also focuses on the dimensions that come as a consequence of these frameworks. How are they articulated around a new social context considering the present and future society, and from where the paradigm should be seen as a conception and direction in education? The educational paradigm is studied as a human and social archetype with four dimensions: Identity, Education, globality and Teckne which is “ the knowledge of doing”